The last Vermeer [videorecording (DVD)] - Friedkin, Dan, 1965-; Pearce, Guy, 1967-; Bang, Claes, 1967-; Krieps, Vicky, 1983-; Lopez, Jonathan (Sony Pictures Home Entertainment, 2021)
After World War II, a former Dutch resistance fighter tries to save the life of a renowned artist and art dealer accused of conspiring with the Nazis because he is convinced of his innocence.